The Role of Stem Cell Therapy in Stroke: A Narrative Review of Scientific Evolution, Clinical Evidence, and Implementation Challenges in Neurology - Michael Aditya Marjoto (International Medical Journal Corp. Ltd, 2026)
Stroke represents a paramount challenge to global public health, standing as a primary cause of mortality and long-term adult disability. In Indonesia, the epidemiological shift toward younger populations and the escalating socioeconomic burden necessitate a transition from traditional neuroprotection to advanced neurorestoration. This narrative literature review provides an exhaustive analysis of the role of stem cell therapy in stroke management, synthesizing four decades of scientific evolution. The report delineates the biological foundations of neurorestoration—including neurogenesis, angiogenesis, synaptogenesis, and immunomodulation—while characterizing various stem cell sources such as mesenchymal stem cells (MSCs), neural stem cells (NSCs), and bone marrow mononuclear cells (BMMNCs). A rigorous methodological assessment using the Cochrane Risk of Bias tool is applied to major clinical trials, including the MASTERS and TREASURE programs. Results indicate that while stem cell therapy demonstrates a robust safety profile and significant improvements in functional activities of daily living (measured by the Barthel Index and NIHSS), consistent global disability reduction (measured by mRS) remains elusive due to a translational disconnect involving dosage, timing, and delivery modalities. Furthermore, this review explores the multifaceted challenges of implementation within neurology practice, particularly in Indonesia, addressing ethical concerns regarding unproven therapies and the critical need for enhanced specialized education for neurologists. The synthesis concludes with strategic recommendations for integrating regenerative medicine into clinical pathways to bridge the current therapeutic gap.